PENERAPAN METODE STORYTELLING UNTUK MENINGKATKAN PERCAYA DIRI DAN KEMAMPUAN BERBICARA SISWA (Studi Pada Kelas X Mata Pelajaran Bahasa Inggris di SMA Negeri 1 Pagar Alam) - Adela Febrina (UNIB Press, 2021)
The aims of this study to: (1) Describe the application of Storytelling method to improve students’ self confidence in SMA Negeri 1 Pagar Alam, (2) Describe the application of Storytelling method can improve students’ speaking skill at SMA Negeri 1 Pagar Alam. The subjects of this study are students of X Social 4 class SMAN 1 Pagaralam. This study was conducted in two cycles by following the procedure of Classroom Action Research, i,e. Planning, Implementing, Observing and Reflecting. Each cycle of the study has two meetings and one test. The data of this study were obtained by using test to measure speaking skill. And Observation sheets to measure students’ self confidence. This research was conducted in class X Social 4 as a PTK class. This study produces conclusions: (1) the application of storytelling method can improve students’ self confidence, (2) the application of storytelling method can improve students’ achievement in speaking, (3) the application of storytelling method effectively increases students’ ability in speaking and their self confidence